2013
DOI: 10.1038/nature11893
|View full text |Cite
|
Sign up to set email alerts
|

Porous materials with optimal adsorption thermodynamics and kinetics for CO2 separation

Abstract: The energy costs associated with the separation and purification of industrial commodities, such as gases, fine chemicals and fresh water, currently represent around 15 per cent of global energy production, and the demand for such commodities is projected to triple by 2050 (ref. 1). The challenge of developing effective separation and purification technologies that have much smaller energy footprints is greater for carbon dioxide (CO2) than for other gases; in addition to its involvement in climate change, CO2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

66
1,628
7
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 2,069 publications
(1,737 citation statements)
references
References 29 publications
66
1,628
7
7
Order By: Relevance
“…mol -1 , F…F dist.= 6.483(1) Å) revealed that the CO 2 is more strongly adsorbed at lower concentrations when the size of the square-shaped channel is further contracted, as a result of the shortened distance between the pendant fluorine moieties from diagonally adjacent (SiF 6 ) 2-pillars. 17,30,31 Considerately, in addition to enabling the MOF pore system characteristics, contracted squareshaped channels with a periodically aligned proximal fluorine moieties, two other parameters were considered for the design and construction of the looked-for hydrolytically stable MOF for carbon capture. Specifically, we elected: i) to employ the Ni(II) as the octahedrally-coordinated metal node since the SIFSIX-3-Ni offers a shorter M-F bond distance (d M-F = 1.99(5) Å) 32 then the SIFSIX-3-Cu (d M-F = 2.12(1) Å) 17 and thus prone to express the requisite water vapor tolerance, and ii) to substitute the (SiF 6 ) 2-pillar with an appropriate fluorinated inorganic pillar, offering a relatively stronger coordination bonds and the adequate nucleophilicity that can preclude the observed phase change in the SIFSIX-3-Cu, associated with the water molecule introduction within the Cu(II) coordination sphere.…”
Section: Resultsmentioning
confidence: 99%
“…mol -1 , F…F dist.= 6.483(1) Å) revealed that the CO 2 is more strongly adsorbed at lower concentrations when the size of the square-shaped channel is further contracted, as a result of the shortened distance between the pendant fluorine moieties from diagonally adjacent (SiF 6 ) 2-pillars. 17,30,31 Considerately, in addition to enabling the MOF pore system characteristics, contracted squareshaped channels with a periodically aligned proximal fluorine moieties, two other parameters were considered for the design and construction of the looked-for hydrolytically stable MOF for carbon capture. Specifically, we elected: i) to employ the Ni(II) as the octahedrally-coordinated metal node since the SIFSIX-3-Ni offers a shorter M-F bond distance (d M-F = 1.99(5) Å) 32 then the SIFSIX-3-Cu (d M-F = 2.12(1) Å) 17 and thus prone to express the requisite water vapor tolerance, and ii) to substitute the (SiF 6 ) 2-pillar with an appropriate fluorinated inorganic pillar, offering a relatively stronger coordination bonds and the adequate nucleophilicity that can preclude the observed phase change in the SIFSIX-3-Cu, associated with the water molecule introduction within the Cu(II) coordination sphere.…”
Section: Resultsmentioning
confidence: 99%
“…CO 2 selectivity is a product of a complex interplay between the porosity (pore size), kinetics and the charge density of the adsorbent. 10 The charge density is directly related to CO 2 interactions with the adsorbent framework. 11,12 (iv) Mild conditions for regeneration: The ability to regenerate the adsorbents is a key parameter in the selection of materials for CO 2 separation.…”
Section: Discussionmentioning
confidence: 99%
“…6 We focus our analysis and discussion on examples of materials (mainly physical adsorbents) that show the best compromise in terms of the intensity of CO 2 energetics 13 as well as the uniformity of interactions. 10 (v) High stability: The adsorbents lifetime, which determines the frequency of their replacement, has a direct impact on the economics of any commercial-scale operation. The stability of the material is a key property that should be considered from the early stage of synthesis and evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…to traditional organics and polymers. [23][24][25][26][27] Drop-on-demand inkjet printer with a nozzle of 20 lm diameter is used to coat the microstructure. Fig.…”
mentioning
confidence: 99%